The First 5 Years Characteristics of Growth and Development of Children Residing in the Regions of Uzbekistan - Dilfuza Ashurova1, O. Tursunova2, N. Nurmatova3, G. Yusupova4, B. Sharapov5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Nutritional issues in children are associated with a complex of factors. Early assistance to thechild is feasible with the on time detection of developing deviations in the health, growth and development.The actual tasks were to determine the level of growth and development of children in the regions of theRepublic of Uzbekistan, assess the effectiveness of programs implemented in the country to improvenutrition and prevent micronutrient deficiency based on the application of new standards for the growth anddevelopment of children, as well as develop relevant proposals and recommendations.Materials and Method: 3969 children under 5 years old living in 6 regions of Uzbekistan were observed.In order to monitor the growth and development of children, anthropometric measurements were carried outin the following periods: the first measurements - at birth, the second and third - at the age of 15 days and1 month, then monthly until the expiration of 12 months, 1 time in 3 months - between 12 and 36 months,every 6 months - between 36 and 60 months and then annually. An immunological study was conducted aswell for children with malnutrition.Results: The percentage of BF in the city of Tashkent was 78.6%, Tashkent region - 66.4%, Khorezm region- 67.3%, Fergana region - 85.7%, Bukhara region - 72.2% and the Republic of Karakalpakstan - 89.0 %Based on those results, it can be stated that in the region where the percentage of IHV was lower (Tashkentand Khorezm regions), the percentage of children with low body weight is greater. By the end of 2012 andthe beginning of 2013, the percentage of children of the first 6 months of life with reduced weight decreasedin all regions. The dynamics of reduced weight by the end of 2012 among children aged 6-12 months waspositiveConclusion: Anthropometric indicators in children of the first 5 years of life, regardless of gender, inalmost all studied regions in terms of body weight and body length/height in most cases were same level. Inchildren under 5 years old, low body weight relative to age prevailed among the forms of impaired physicaldevelopment and nutrition in all regions.